2008
DOI: 10.1007/s11829-008-9048-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of wheat and barley to Russian wheat aphid, Diuraphis noxia (Mordvilko) and bird cherry-oat aphid, Rhopalosiphum padi (L.) (Hemiptera: Aphididae)

Abstract: Although aphids are among the most injurious of all agronomic insect pests, much remains unknown about how their feeding alters plant physiology. Two experiments were conducted to examine the physiological responses of wheat, Triticum aestivum L. and barley, Hordeum vulgare L. to injury by Diuraphis noxia (Mordvilko) and Rhopalosiphum padi (L.) (Hemiptera: Aphididae). Gas-exchange parameters, chlorophyll fluorescence, and chlorophyll content were examined at 3, 6, and 9 days post-infestation on control and aph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Perhaps the partial resistance present in cv. Kardal young leaves, similar to what Pierson et al (2010) and Franzen et al (2008) have found in other plant-aphid combinations, relies on the ability of the leaves to maintain the photosynthesis rate. Cottrell et al (2009) found that black pecan aphid-induced leaf chlorosis plays an important role in the interaction of the aphid with its host.…”
Section: Downregulated Genessupporting
confidence: 59%
See 2 more Smart Citations
“…Perhaps the partial resistance present in cv. Kardal young leaves, similar to what Pierson et al (2010) and Franzen et al (2008) have found in other plant-aphid combinations, relies on the ability of the leaves to maintain the photosynthesis rate. Cottrell et al (2009) found that black pecan aphid-induced leaf chlorosis plays an important role in the interaction of the aphid with its host.…”
Section: Downregulated Genessupporting
confidence: 59%
“…() and Franzen et al . () have found in other plant–aphid combinations, relies on the ability of the leaves to maintain the photosynthesis rate. Cottrell et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS mediate different signaling pathways that are associated with plant defense mechanisms, and play roles as secondary messengers in hormone signaling pathways (Alvarez, 2000;Franzen et al, 2008). In addition, SA increases hydrogen peroxide (H 2 O 2 ) generation (Tewari and Paek, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The SPAD meter has been successfully used to estimate nitrogen concentration in rice leaves and to guide nitrogen management in rice paddies (Hussain et al 2000;Huang et al 2008;Gholizadeh et al 2009). Franzen et al (2008) found that SPAD readings in wheat (at the fourth leaf stage) were reduced when infested with fifteen aphids for 6 and 9 days. Degree of damage of sorghum by greenbugs could be detected indirectly by the chlorophyll content of leaves, and the linear relationship between SPAD values and actual chlorophyll losses was significant (Deol et al 1997).…”
Section: Introductionmentioning
confidence: 96%